Pediatric Covid-19 Patients Laboratory Characteristics in Dr.Ramelan Central Navy Hospital: A-Year Epidemiology Study - RETNO WISANTI; RUSDIAN NIATI NINGSIH (HANG TUAH MEDICAL JOURNAL, 2022)
Covid-19 in children has several different characteristics with the adults, from clinical manifestation to laboratory result. There is also challenges in Covid-19 diagnosis in children with their inability to describe their condition clearly. Laboratory examination used to confirm the diagnosis, but the accuracy still in doubt. We aims to describe the laboratory examination result of pediatric Covid-19 patients. We analyze the medical records of 69 children with suspect Covid-19 who hospitalized in isolation room in a year period, from May 2020 to April 2021. All of the suspect patient were examined by PCR test, rapid antibody test, chest x-ray, and complete blood count. 40 patients were Covid-19 positively-confirmed by the PCR test. Chest x-ray gave better sensitivity and specificity for early screening than rapid antibody test. The complete blood count gave normal results in general, only slight relative lymphocytosis occurred. The neutrophilia and lymphopenia pattern in adults with Covid-19 are different with the children’s result. The increase of NLR, who commonly used as an early screening test in adult Covid-19, cannot be used in children. The lower inflammatory response and physiologically higher lymphocyte cell count in younger age explain these results. In conclusion, the laboratory test should be performed for pediatric Covid-19 cases, but not for confirm the diagnosis.